Advances in Prostate‐Specific Membrane Antigen (PSMA)‐Targeted Phototheranostics of Prostate Cancer. Issue 8 (10th May 2022) - Wang, He; He, Zhangxin; Liu, Xiao-Ang; Huang, Yuhua; Hou, Jianquan; Zhang, Weijie; Ding, Dan
Abstract : With the advent of the era of precision medicine, prostate‐specific membrane antigen (PSMA)‐targeted theranostic strategies have had a profound impact on prostate cancer research. As a specific membrane antigen target, PSMA is not only widely expressed in prostate cancer tissues but its expression is also correlated with tumor aggressiveness. Because of the noninvasiveness, real‐time nature, high sensitivity, and low side effects of phototheranostics, in recent years, there has been a rapid advancement in PSMA‐targeted phototheranostics, such as near‐infrared fluorescence imaging and imaging‐guided surgical navigation, photoacoustic imaging, dual‐modality hybrid imaging and imaging‐guided surgical navigation, photodynamic therapy, and photothermal therapy. Herein, the design and application of various types of imaging probes and photosensitizers based on PSMA targeting developed in the past two decades are reviewed, with a focus on molecular design strategies for near‐infrared fluorescent probes and hybrid tracers. In addition, the challenges of and future opportunities for the clinical translation of phototheranostics in the field of prostate cancer are discussed. Abstract : The application and progress of prostate‐specific membrane antigen (PSMA)‐targeted for phototheranostics of prostate cancer are reviewed. The design principles and advantages of PSMA‐based targeted optical imaging probes and the future design directions of photosensitizers for phototherapy are summarized. The aim herein is to accelerate the preclinical research and clinical translation of PSMA‐based phototheranostics for prostate cancer.